Acute haemodynamic changes during haemodialysis do not exacerbate gut hyperpermeability. Issue 4 (12th April 2019) - Wong, Jonathan; Lenaerts, Kaatje; Meesters, Dennis M.; Olde Damink, Steven W.M.; van Eijk, Hans M.H.; Vilar, Enric; Farrington, Ken
Abstract : Introduction: The gastrointestinal tract is a potential source of inflammation in dialysis patients. In vitro studies suggest breakdown of the gut barrier in uraemia leading to increased intestinal permeability and it is hypothesised that haemodialysis exacerbates this problem due to mesenteric ischaemia induced by blood volume changes during treatment. Method: The effect of haemodialysis on intestinal permeability was studied in ten haemodialysis patients and compared with five controls. Intestinal permeability was assessed by measuring the differential absorption of four orally administered sugar probes which provides an index of small and whole bowel permeability. A multi-sugar solution (containing lactulose, rhamnose, sucralose and erythritol) was orally administered after an overnight fast. Plasma levels of all sugar probes were measured hourly for 10 h post-administration. In haemodialysis patients, the procedure was carried out twice — once on a non-dialysis day and once immediately after haemodialysis. Results: Area under curve (AUC) for lactulose:rhamnose (L:R) ratio and sucralose:erythritol (S:E) ratio was similar post-dialysis and on non-dialysis days. AUC for L:R was higher in haemodialysis patients compared with controls (0.071 vs. 0.034, P =0.001), AUC for S:E ratio was not significantly different. Levels of lactulose, sucralose and erythritol were elevated and retained longer in haemodialysis patients compared with controls due to dependence of sugars on kidney function for clearance. Conclusion: We found no significant acute changes in intestinal permeability in relation to the haemodialysis procedure. Valid comparison of intestinal permeability between controls and haemodialysis patients was not possible due to the strong influence of kidney function on sugar levels.